Theoretical and simulation analysis on the spatial resolution of magnetic metal debris sensors - Ren, Yijun; Wen, Xiaolong; Gao, Shengwei; Liu, Yongbin; Ju, Bin (Frontiers in Materials, 2023)
Inductive debris sensor is becoming increasingly important in online oil debris detection. This work proposes a new criterion for evaluating the performance of an inductive oil debris sensor: spatial resolution. When multiple metal particles in lubricating oil simultaneously pass through the sensor, it is vital that clear signals responding to each particle are produced. The spatial resolution is referred to the allowable distance between two particles when the sensor can accurately distinguish the particle signals. Theoretical analysis shows that spatial resolution has a relationship with the output signal of a single particle. A COMSOL model is established to simulate a coil output when two adjacent particles pass, and the output signals change with the distance between two particles, the particle size and the coil structures. Results show that the relevant factors affecting the spatial resolution, and a small coil radius can help improve the sensor’s accuracy of debris identification.